2022
DOI: 10.3389/fonc.2022.833195
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sexual and Gender Minority Cancer Care: Patient and Caregiver Perspectives From a Multi-Methods Pilot Study

Abstract: PurposeUp to 1 million lesbian, gay, bisexual, and transgender (i.e., sexual and gender minority, SGM) individuals in the United States have histories of cancer. This medically underserved population is diverse, with complex sexualities and gender identities, and distinct health concerns. SGM persons experience disproportionate risks for, and rates of, anal, breast, cervical, colorectal, endometrial, lung, and prostate cancers, in addition to cancers affecting transgender persons who have undergone sex-reassig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…A similar notion of increased appraisal and general support was identified in a recent survey study in young adult SGD patients when compared to cisgender heterosexual patients [22]. Additional findings from a multimethods study highlighted that SGD cancer patients appear to report lower pain and fatigue intensities than heterosexual cancer patients [23 ▪ ]. Lastly, SGD patients often appear to maintain effective strategies for self-advocacy and resiliency despite the challenges and disparities they face due to often underlying cis-heteronormativity in cancer care [24 ▪▪ ,25].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…A similar notion of increased appraisal and general support was identified in a recent survey study in young adult SGD patients when compared to cisgender heterosexual patients [22]. Additional findings from a multimethods study highlighted that SGD cancer patients appear to report lower pain and fatigue intensities than heterosexual cancer patients [23 ▪ ]. Lastly, SGD patients often appear to maintain effective strategies for self-advocacy and resiliency despite the challenges and disparities they face due to often underlying cis-heteronormativity in cancer care [24 ▪▪ ,25].…”
Section: Resultssupporting
confidence: 61%
“…However, when their mental health needs are met, and they receive social support, their odds of depression appear to be significantly lower [30 ▪ ]. Other factors affecting SGD survivors include more social isolation in comparison to cisgender heterosexual survivors [23 ▪ ]. Particularly during the COVID-19 pandemic, SGD patients felt isolated especially when caregivers were not able to visit according to one study [31].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the United Kingdom and Australia have focused on examining sexual minorities’ satisfaction with cancer care (Hulbert-Williams et al, 2017; Ussher et al, 2022) pointing to dissatisfaction with care. However, qualitative studies and quantitative studies of sexual minority cancer survivors in the United States report both dissatisfaction with care and rating care as more favorable compared with heterosexual cancer survivors (Boehmer et al, 2020; Kano et al, 2022; Lisy et al, 2018). Trust in providers and encountering respectful and culturally trained providers have been linked to greater satisfaction with care, whereas discrimination and unmet needs have been linked to poor satisfaction with care (Kano et al, 2022; Lisy et al, 2018; Ussher et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, qualitative studies and quantitative studies of sexual minority cancer survivors in the United States report both dissatisfaction with care and rating care as more favorable compared with heterosexual cancer survivors (Boehmer et al, 2020; Kano et al, 2022; Lisy et al, 2018). Trust in providers and encountering respectful and culturally trained providers have been linked to greater satisfaction with care, whereas discrimination and unmet needs have been linked to poor satisfaction with care (Kano et al, 2022; Lisy et al, 2018; Ussher et al, 2022). In this study, none of the sexual minority–specific characteristics related to rating care as excellent, which may support the interpretation of an earlier study (Boehmer et al, 2020) that sexual minorities have trepidations about the care they will receive and are relieved when their fears prove unwarranted.…”
Section: Discussionmentioning
confidence: 99%
“…Single-institution studies have identified elevated rates of distress in rural (Burris & Andrykowski, 2010) and Hispanic (Fayanju et al, 2021;Gonzalez et al, 2022) breast cancer survivors, whereas mental health diagnosis and treatment after a cancer diagnosis appear to be more accessible to White, non-Hispanic patients (Chen et al, 2022). Adverse experiences with the health care system, including medical mistrust and experience of discrimination, may be more salient for minoritized populations and should be included in assessment of distress (Kano et al, 2022;Sheppard et al, 2014).…”
Section: Future Directionsmentioning
confidence: 99%